LIBRARY LITERACY MANAGEMENT IN MOTIVATING STUDENTS' INTEREST IN READING AT DRIVING SCHOOLS IN STATE JUNIOR HIGH SCHOOLS BARITO KUALA - Mayasari; Husnul Madihah; Agustina Rahmi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The purpose of this study is to find out  the literacy management of school libraries, supporting and inhibiting factors, and strategies that can be applied by the library in an effort to motivate students' interest in reading at SMPN 3 Alalak and SMPN 4 Alalak as driving schools.The theory used in this study is the theory according to George R Terry. The methodology of this research uses a qualitative approach and this type of research uses qualitative descriptive research. Data collection techniques through observation, interviews, and documentation. The results of the study show that library management in SMPN 3 Alalak and SMPN 4 Alalak in motivating students' interest in reading includes the function of Planning is the development of collections and reference services. The Organizing Function is the division of library work programs and reference services. The function of Direction/implementation is the development of collections. The supervisory function is collaboration and partnership. Supporting and inhibiting factors to motivate students' interest in reading at SMPN 3 Alalak and SMPN 4 Alalak as driving schools include technological advancements, collection of reading materials, human resources, facilities and infrastructure. Strategies that can be applied by the library in motivating students' interest in reading as a driving school are increasing collection materials, providing adequate facilities and infrastructure, providing good services, holding additional programs such as conducting regular and continuous promotions. It can be concluded that at the end of the study, data was obtained for student visits to the SMPN 3 Alalak library reaching 27%, which is not yet classified as high student visits, while for SMPN 4 Alalak reaching 65%, it is classified as high student visits.